2017
DOI: 10.1097/jcn.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Food Costs Are Higher in Counties With Poor Health Rankings

Abstract: Background: Poor dietary habits are associated with higher rates of cardiovascular disease. However, the cost of foods associated with lower risk of cardiovascular disease can be a significant barrier to healthy eating. Objective: The aim of this study is to determine whether food prices per serving differed across Kentucky counties based on health ranking and overall nutritional quality. Methods: Fifteen co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…with four of these studies supplementing the data with online supermarket prices [62][63][64]81]. Additionally, three instruments compared the cost of a 'healthy diet' to either an 'unhealthy or currently consumed diet' [20,88,110], 13 instruments compared the cost of 'healthy' and 'unhealthy' individual foods or product categories [19,38,51,62,63,66,83,87,89,90,103], and 14 instruments did not present a comparison [37,40,46,49,50,52,64,67,70,80,81,91,92,104,105]. 'Current' diets were defined using national survey data [20,110].…”
Section: Nems-s Nutrition Environment Measures Survey-storesmentioning
confidence: 99%
See 2 more Smart Citations
“…with four of these studies supplementing the data with online supermarket prices [62][63][64]81]. Additionally, three instruments compared the cost of a 'healthy diet' to either an 'unhealthy or currently consumed diet' [20,88,110], 13 instruments compared the cost of 'healthy' and 'unhealthy' individual foods or product categories [19,38,51,62,63,66,83,87,89,90,103], and 14 instruments did not present a comparison [37,40,46,49,50,52,64,67,70,80,81,91,92,104,105]. 'Current' diets were defined using national survey data [20,110].…”
Section: Nems-s Nutrition Environment Measures Survey-storesmentioning
confidence: 99%
“…'Current' diets were defined using national survey data [20,110]. Level of healthiness was defined using various benchmarks, namely the NOVA food processing classification system [38], nutrient composition and energy density [38,51,62,63,66,80,83,90], national Dietary Guidelines [19,43,70,[87][88][89][90], and the Dietary Approaches to Stop Hypertension (DASH) dietary pattern [43]. Food affordability was benchmarked using household income [20, 49, 50, 90-92, 103, 105, 110], government subsidies [37,40,87,89,91], and minimum wage [38,66,70]; however, most studies (n = 13) did not determine relative affordability in their analysis [43, 51, 52, 55, 62-64, 67, 73, 80, 81, 83, 88].…”
Section: Nems-s Nutrition Environment Measures Survey-storesmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of West Virginia census data found that total number of food stores, business establishments, and mean travel time to work increased rates of obesity among the population [83]. The limited food access in these areas are in part due to rural locality, lower income in the state and lack of vehicle access [74,83,145,[167][168][169]. As dietary change is a common recommendation for weight loss, for those in a health disparate population with limited access to food, following a prescribed or suggested dietary pattern for health purposes may be difficult to achieve and near impossible to sustain [170].…”
Section: Introductionmentioning
confidence: 99%